Investigation of bias polarity dependence of set operation in GeCu2Te3 phase change memory. Issue 6 (1st March 2018) - An, J.S.; Kim, K.J.; Choi, C.M.; Shindo, S.; Sutou, Y.; Song, Y.H.
Abstract : We measured the impact of the thermoelectric effect, especially the Peltier effect, upon the operation of phase change memory (PCM) in which the contact resistance between the phase change material and the electrode dominates the total resistance. A PCM device having a pillar structure of diameter 500 nm was fabricated using GeCu2 Te3 (GCT) material. During read operation, the set state (with crystalline PCM) showed ohmic contact between the PCM and the electrode, whereas the reset state (with amorphous PCM) showed Schottky contact. The Schottky contact between the amorphous GCT and the electrode showed a bias polarity dependence of set operation owing to the Peltier effect, which is one of the thermoelectric effects. As PCM devices scale down to the nanometre scale, research on contact resistance and various related effects will become more important.